1997
DOI: 10.1515/cclm.1997.35.9.655
|View full text |Cite
|
Sign up to set email alerts
|

Substance P Induces the Secretion of Gelatinase A from Human Synovial Fibroblasts

Abstract: Summary: We investigated the secretion of the matrix metalloproteinases, interstitial collagenase (matrix metalloproteinase-1), gelatinase A (matrix metalloproteinase-2) and stromelysin-1 (matrix metalloproteinase-3) in human synovial fibroblasts after stimulation with the neuropeptide substance P.Human synovial fibroblasts were stimulated with substance P or interleukin-lß (IL-lß). In the cell culture media gelatinase A, interstitial collagenase and stromelysin-1 were identified and their activities towards d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
7
0
1
Order By: Relevance
“…This activation, in turn, would allow release of the chemokine domain of fractalkine from neurons. Although no studies to date have examined the conditions under which matrix metalloproteinases in spinal cord are activated, it is known that substances critically involved in pain enhancement in the dorsal horns (excitatory amino acids, substance P, nitric oxide, prostaglandin E2) can each activate matrix metalloproteinases in other systems (Hecker‐Kia et al ., 1997; Lyons et al ., 2002; Szklarczyk et al ., 2002; Mayers et al ., 2003). If these substances can also activate matrix metalloproteinases in spinal cord, then their release in response to peripheral inflammation and injury could potentially lead to the activation of matrix metalloproteinases expressed by neurons, astrocytes and/or microglia (Cross & Woodroofe, 1999; Szklarczyk et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This activation, in turn, would allow release of the chemokine domain of fractalkine from neurons. Although no studies to date have examined the conditions under which matrix metalloproteinases in spinal cord are activated, it is known that substances critically involved in pain enhancement in the dorsal horns (excitatory amino acids, substance P, nitric oxide, prostaglandin E2) can each activate matrix metalloproteinases in other systems (Hecker‐Kia et al ., 1997; Lyons et al ., 2002; Szklarczyk et al ., 2002; Mayers et al ., 2003). If these substances can also activate matrix metalloproteinases in spinal cord, then their release in response to peripheral inflammation and injury could potentially lead to the activation of matrix metalloproteinases expressed by neurons, astrocytes and/or microglia (Cross & Woodroofe, 1999; Szklarczyk et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In human synovial fibroblasts, Hecker‐Kia et al . have shown that Substance P stimulation significantly enhanced secretion of MMP‐2, whereas no significant increase of MMP‐1 and ‐3 secretions was observed (35).…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of TIMP-1 seems to differ from that of the MMPs, particularly in terms of induction by cytokines in gingival fibroblasts (34). In human synovial fibroblasts, Hecker-Kia et al have shown that Substance P stimulation significantly enhanced secretion of MMP-2, whereas no significant increase of MMP-1 and -3 secretions was observed (35).…”
Section: Discussionmentioning
confidence: 99%
“…Inoue et al (2001) suggested that bFGF plays an important role as an inductor or a promoter for the production of substance P in synovial fibroblasts derived from patients with RA and OA. Substance P is known as a potent mediator of inflammation in various tissues because it promotes the secretion of IL‐1 and TNFα in monocytes (Kimball et al, 1988; Lotz et al, 1988); it also stimulates synovial cells to produce prostaglandin E 2 (PGE 2 ), MMPs (Lotz et al, 1987; Hecker‐Kia et al, 1997) and reactive oxygen species (ROS) (Tanabe et al, 1996). However, the biological function(s) of substance P or its receptor in articular chondrocytes is not clear.…”
mentioning
confidence: 99%